FEBRILE INFECTION-RELATED EPILEPSY SYNDROME: A RARE CASE PRESENTATION - James, Aloysius; Reji, Reshma; Vincent, Bini; Mani, Nimmu; Reghu, Remya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Febrile infection-related epilepsy syndrome is characterized by super refractory status epilepticus that is resistant to conventional antiepileptic drugs. This case report critically analyses the treatment options adopted in a hospital to manage this syndrome. Despite the aggressive efforts that were taken, the patient succumbed to the complications of the illness and side effects of the treatment strategies adopted. This shows that the treatment options currently available are in adequate, so an intensive research in the area of pathogenesis of status epilepticus is required to frame treatment strategies that can bring out better outcomes. Keywords: Antiepileptics, Febrile infection-related epilepsy syndrome, Status epilepticus.